2005
DOI: 10.1007/s11199-005-8309-z
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Barriers in Athletic Administration: An Analysis of Job Descriptions for Interscholastic Athletic Directors

Abstract: The purpose of this study was to determine if the job descriptions for interscholastic athletic directors (AD) used by school districts contained some form of gender bias that might deny women the opportunity to compete for those positions. Job descriptions were collected from 112 school districts within the state of Texas. A content analysis of each job description showed that 17% of the job descriptions listed as a qualification that the AD also serve as the head football coach (HFC). The link between the AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
1
17
0
3
Order By: Relevance
“…Analyses of the decision-making committees in sport organizations have revealed the extent to which women are excluded from leadership positions in Canada , Denmark (Ottesen et al, 2010), Germany (Pfister & Radtke, 2009), Sweden (Ottesen et al, 2010), and the US (Acosta & Carpenter, 2000;Whisenant et al, 2005). A study of nearly 70 Canadian national sport organizations revealed that although nearly half of the entry-level positions were held by women, they comprised 28% of the executive directors, 23% of the technical directors, and less than 10% of the national coaches .…”
Section: Attitudes Toward Female Managersmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of the decision-making committees in sport organizations have revealed the extent to which women are excluded from leadership positions in Canada , Denmark (Ottesen et al, 2010), Germany (Pfister & Radtke, 2009), Sweden (Ottesen et al, 2010), and the US (Acosta & Carpenter, 2000;Whisenant et al, 2005). A study of nearly 70 Canadian national sport organizations revealed that although nearly half of the entry-level positions were held by women, they comprised 28% of the executive directors, 23% of the technical directors, and less than 10% of the national coaches .…”
Section: Attitudes Toward Female Managersmentioning
confidence: 99%
“…Studies on under-representation of women in sport organizations have also suggested that there are far fewer women than men in senior positions in sport organizations (e.g., Acosta & Carpenter, 2000;Chen & Henry, 2012;Hall, Cullen, & Slack, 1990;Hovden, 2000;Ottesen, Skirstad, Pfister, & Habermann, 2010;Pfister & Radtke, 2009;Whisenant, Miller, & Pedersen, 2005). These studies showed that dominant discourses about sport valorize masculine qualities, such as mental and physical toughness and competitiveness (Messner, 2002), and that dominant discourses about managerial roles in sport organizations have always been allied with the constructions of masculinities within the sporting context.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps it would be useful to begin with a careful analysis of job descriptions and job announcements and how they might influence the hiring process. In a study examining the content of job descriptions for athletic directors in Texas, Whisenant et al (2005) found 17% of the job descriptions listed Head Football coach as a qualification for the athletic director position being advertised. Further, Whisenant (2005) found that in Texas, 77% of the athletic director job announcements for a one year period required that applicant also serve as the school's head football coach.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of publications utilizing job descriptions reveals that the holistic approach to analysis of the past resulted in a substantial body of research designed to investigate professional job advertisements, including librarian job announcements, to determine what a job is and to identify ideal job competencies. For example, Whisenant, Miller, and Pedersen (2005) studied job descriptions for interscholastic athletic directors used by school districts to identify forms of gender bias that might deny women opportunities to complete for positions. In a content analysis, investigated roles and competencies sought for metadata professionals.…”
Section: Literature Reviewmentioning
confidence: 99%